Examination of Parties to Electronic Litigation in the Religious Courts - A. Rizqon Faghfirli (International Journal of Law, Environment, and Natural Resources, 2023)
Electronic courts provide convenience to justice seekers starting from registration, summons, and trial proceedings. On the other hand, electronic trials will also have implications for the effectiveness and efficiency of the litigation process, so that not much time is wasted and costs are not incurred. However, it is interesting to analyze in fact that in Supreme Court Regulation Number 7 of 2022 the author does not find any rules governing the procedures for examining one of the litigants who do not agree to conduct electronic trials, in the case of electronic trials (e-Litigation) Court Regulations Agung Number 7 of 2022 only regulates the exchange of response documents, replicas and duplicates from the parties electronically as well as arrangements for examining witnesses or experts which can be carried out remotely through electronic audio-visual communication media. So a party who refuses an electronic trial is deemed not to have exercised his rights so this is detrimental to that party, there is no procedure available for that party to continue to exercise his rights.